HUBUNGAN PENGETAHUAN IBU TENTANG MANAJEMEN LAKTASI DENGAN PEMBERIA ASI ESKLUSIF DI DESA KADUGEMBLO PANDEGLANG TAHUN 2020 - Hadi Nugroho; Agnes Agesti (STIKes IMC Bintaro, 2021)
Introduction factor contributing to the high IMR one of which is the low coverage of exclusive breastfeeding, because no exclusively breastfed infants are more vulnerable are exposed to various diseases that increase morbidity and mortality. The purpose of study this was to determine the relationship between maternal knowledge about lactation management and exclusive breastfeeding in Kadugemblo Village Pandeglang in 2020. The research method used case control with the sampling technique using quota sampling with a total sample of 46 respondents. The sample in this study were all mothers who breastfed their babies in Kadugemblo Village.test Statistical using Chi square. The results showed that the majority of mothers who exclusively breastfed their babies were 23, 50.0%) and mothers who did notbreastfeed exclusively were 23 respondents (50.0%). Chi-squaretest p value gain of 0.074 to p <0.05, which means Ha rejected. So it can be concluded that there is no relationship between maternal knowledge about lactation management and breastfeeding exclusive.